Management Practices To Minimise Calf Mortality In Buffaloes (Bubalus Bubalis) - Shrivastava , M.; Nanavati, S.; Yadav, D.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The data on mortality of buffalo calves were collected by random survey methods from 100 farmers from thirteen villages. . The data were classified according to land and animal holding, educational level, duration of colostrum feeding after birth, age and sex of calf, parity of dam and causes of mortality. The highest mortality in buffalo calves was recorded due to gastroenteritis (34.68%), followed by worm infestation (24.06%). On the basis of the various causes of mortality observed in the survey work, a package of practices was developed and applied to minimize the calf mortality in buffaloes. It was observed that in the treatment group (10 buffalo calves), where the package of practices was applied, no death was observed during entire period of experiment , whereas in control group out of 10 buffalo calves, 3 calves (two due to enteritis and one due to worm infestation) were died.
Keywords: Calf mortality; Package of practices; Buffaloes